Analisis juridico, doctrinario y de campo del principio de proporcionalidad de la pena en los delitos de muerte culposa de transito en el codigo organico integral penal ecuatoriano - Salinas Cueva, Sergio Alipio (2014)
The principle of proportionality says among other things, that the punishment must be proportionate to the criminal act. The principle of proportionality is the idea of avoiding an excessive use of penalties involving deprivation or restriction of freedom for this use is limited to what is necessary is nothing but establish them and impose solely to protect legal interests valuable, in this case the State is obliged to protect the legal right of life. Hence the question arises there is real weight when it comes to protecting life, between the penalty imposed who drives a vehicle while intoxicated or narcotic drugs or psychotropic substances and kills one or more persons with the leading a vehicle for speeding, failure to comply with laws and regulations or other circumstances and causes the death of one or more people? The accident is considered a criminal offense, but a guilty criminal offense, ie, it is a crime with no malice. Intentional crimes are those in which the author has not planned, organized and thought crime. So, what mediates these types of crimes are un necessary, dangerous and illegal actions by the person charged as criminally responsible for the act. A described as the second paragraph of Article 377 of the Penal Code of Integral. In other words, the author did not want to crash an accident. Given the above described problem I decided to develop this research work entitled "ANALYSIS LEGAL, doctrinaire AND FIELD OF THE PRINCIPLE OF PROPORTION TO THE DEATH IN THE CRIMES OF DEATH WRONGFUL TRAFFIC IN CODE ORGANIC COMPREHENSIVE CRIMINAL ECUATORIANO" in which I analyze the doctrinal and legal issues raised, achieving demonstrate the failure of the law and the urgent need to reform the statute invoked before since it is in contrast to the established by the Constitution. Therefore in this work the theoretical arguments, results of field research, in which analysis the need to reform the Articles 376 and 377 of the Penal Code of Integral order to establish the principle of proportionality of the penalty collected is shown in crimes transit wrongful death, and this is the main idea of my thesis, which I hope will help to solve this problem.